A Review on NiTiCu Shape Memory Alloys: Manufacturing and Characterizations - Mohammed, Safar; Qadır, Razaw; Kök, Mediha; Qader, Ibrahim (Niyazi BULUT, 2021)
Shape memory alloys have the thermoelastic phase transformation, known as shape memory characteristics, which make them be used in wide technological applications compared to other alloys. Ni-Ti based SMAs compared to the other families have more applications especially in the biomedical field since they have high biocompatibility, high strain recovery, flexibility, and antirust. In this work, the studies conducted for NiTiCu SMAs were reviewed. Additionally, different manufacturing techniques used by researchers have been explained. Different characteristics of the alloys have been clarified and compared with some other families.
Keywords: Material Production Technologies; Malzeme Üretim Teknolojileri